Congenital Anophtholmos In Newborn-A Rarity - P.PARAMANANTHAM; R.ILAYARJA; S.V.SWAMY RAJ; RADHAKRISHNAN PAULRAJ (International Journal of Pharma and Bio Sciences, 2012)
True Anophtholmos occurs when the primary optic vesicle fails to grow out from the cerebral vesicle during early embryologic development. Anophtholmos most often is bilateral, except for rare instances when one eye is microphthalmic and the other anophthalmic. The orbit and eyelids are usually small but well formed. The conjunctival fornices are decreased in size, and the eye cannot be felt in the orbit on palpation. The socket and hypoplastic orbits should be treated with socket expansion with progressively enlarging conformers until prosthesis can be placed congenital Anophtholmos is a very rare condition that has a reported prevalence rate of 0.18per 10,000 births in United States. This case is imported because of its rarity.